Pemaknaan Melalui Konstruksi Sosial Yang Dibangun Oleh Wartawan Dalam Menyebarkan Ujaran Melalui Facebook - Liza Diniarizky Putri; Annisarizki Annisarizki; Rahmi Mulyasih (LONTAR: Jurnal Ilmu Komunikasi, 2019)
Social media has an its implications for the democratization of information, because anyonewho owns the account can be a prosumer (producer and consumer) in creating messages,however the low control mechanisms are still causing the content in social media is not onlypositive, but also negative, such as spreading hate speech. Hate speech also coloring thesocial media account of journalists in Banten, especially during the Banten electioncampaign of Governor in 2017. This research is to uncover the meaning of journalist to theproffesion and media they manage in utter hatred speech which they spread throuh facebookin Governor Election of Banten 2017, and it was conducted by qualitative research methodthrough phenomenology research approach. By using Social Construction Theory as aframing of qualitative analysis.